Kuwaiti government initiatives and efforts towards nationalizing labor market - Saied, Muna H.; Shuriye, Abdi Omar (The Islamic Centre for Research and Development Inc. Sydney, Australia, 2018)
The immigration rate in the Gulf Cooperation Council states (GCC) has reached such levels that locals have become a minority in the private labor force in every Gulf Cooperation Council state except Saudi Arabia. Even after the initiation of nationalization policies, this remains the case, and Kuwait is no exception. According to the latest statistics from the Kuwait Public Authority for Civil Information, the population of Kuwait hosts about 2.8 million expatriates compared to a local population of about 1.3 million citizens. Kuwait’s dependence on expatriates has created both opportunities and challenges for the employment of Kuwaitis in the private sector. The expatriates are visible at almost every economic activity ranging from high-tech engineering projects to simple daily transactions. However, the unexpectedly high growth in population has resulted in demographic imbalances particularly when it comes to the gender ratio. Limited research has been conducted on the Gulf Cooperation Council states in general and on Kuwait in particular in term of efforts at preparing nationals or local citizens for entry into the skilled workforce. Therefore, this paper focuses on government initiatives and efforts in supporting local labor to replace the foreigner’s works at different sector. In term of organization, this paper aims to explore the new Economic and Political initiatives of Kuwait government for replacement policy. The paper will also explain the forms of Kuwaitis reluctance of working in both public and private sectors. Moreover, it discusses the current practice of replacement policy in Kuwait. The final section of the paper presents the summary. The research reveals some facts, among which are: 1- Kuwait’s dependence on public sector jobs is more intense than other GCC countries, with 75.8% of Kuwaiti employees working for the government. 2- The approach that Kuwait took to nationalize its private labor market coincides with the one followed by other GCC countries, but with the difference that the Kuwaiti law takes into account the nature of different sectors. 3- The Kuwaiti workforce is still concentrated in the public sector whilst migrant manpower dominates the private sector, thus, become the dominant demographic group in society.